FAKTOR – FAKTOR YANG MENYEBABKAN ANAK PUTUS SEKOLAH DI DESA PULAU SIPAN KECAMATAN INUMAN KABUPATEN KUANTAN SINGINGI - Papin Indra Yeni; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Education is very important in the face of this era, and the school is a learning container children ranging from elementary school, junior high, high school and to university. In Indonesia has been in the compulsory school 9 (nine) years, but until now there are still many children out of school in the village of Sipan P Ulau Inuman District of Kuantan District Singingi ranging from elementary and junior high school level that causes a variety of factors. The school drop out by comparing the economic factor family, his own volition and environmental factors. This research was conducted in the village of Sipan Island Kecematan Inuman Singingi Kuantan District, this research especially in children dropping out of school with the aim to analyze the causes or factors that lead to children dropping out of school. The samples in this study using census with certain considerations. Census techniques in this study because of the amount of a population of a little, so that the entire population sampled. The number of samples in this study as many as 42 people, consisting of 20 elementary schools and 22 junior high school level. Data collection techniques in this study is the observation and interviews, types and sources of data used are primary data and secondary data. The data is analyzed by qualitative descriptive analysis, which is presented in tabular form in accordance with the characteristics of each data. The conclusion from this study is that many children are dropping out of school at junior high school level and causes of dropout occurs largely because they factor in measuring economic families of indicators causes of school dropouts. Key Words :Activity, social,children